Systemic depletion of macrophages in the subacute phase of wound healing reduces hypertrophic scar formation. Issue 4 (14th June 2016) - Zhu, Zhensen; Ding, Jie; Ma, Zengshuan; Iwashina, Takashi; Tredget, Edward E.
Abstract: Hypertrophic scars are caused by trauma or burn injuries to the deep dermis and can cause cosmetic disfigurement and psychological issues. Studies suggest that M2‐like macrophages are pro‐fibrotic and contribute to hypertrophic scar formation. A previous study from our lab showed that M2 macrophages were present in developing hypertrophic scar tissues in vivo at 3–4 weeks after wounding. In this study, the effect of systemic macrophage depletion on scar formation was explored at subacute phase of wound healing. Thirty‐six athymic nude mice that received human skin transplants were randomly divided into macrophage depletion group and control group. The former received intraperitoneal injections of clodronate liposomes while the controls received sterile saline injections on day 7, 10, and 13 postgrafting. Wound area, scar thickness, collagen abundance and collagen bundle structure, mast cell infiltration, myofibroblast formation, M1, and M2 macrophages together with gene expression of M1 and M2 related factors in the grafted skin were investigated at 2, 4, and 8 weeks postgrafting. The transplanted human skin from the control group developed contracted, elevated, and thickened scars while the grafted skin from the depletion group healed with significant less contraction and elevation. Significant reductions in myofibroblast number, collagen synthesis, and hypertrophic fiber morphology as well as mast cell infiltration were observed in the depletion group compared to the control group. Macrophage depletion significantly reduced M1 and M2 macrophage number in the depletion group 2 weeks postgrafting as compared to the control group. These findings suggest that systemic macrophage depletion in subacute phase of wound healing reduces scar formation, which provides evidence for the pro‐fibrotic role of macrophages in fibrosis of human skin as well as insight into the potential benefits of specifically depleting M2 macrophages in vivo.